(untitled) (Journal of Surgical Sciences, 2019)
Objective: Appendectomy, being the most common surgical procedure performed in general surgery, is still being performed by both open and laparoscopic methods due to a lack of consensus as to which is the most appropriate method. Because further trials are necessary and few such studies have been performed in developing countries, we decided to evaluate the outcomes of the 2 procedures to share our experience with others. Methods: Prospectively collected data from 618 consecutive patients with appendicitis were studied. These comprised of 340 patients who underwent conventional open appendectomy and 260 patients treated laparoscoplcally&18 were excluded because of protocol violations. The two groups were compared with respect to operative time, length of hospital stay, postoperative pain, return to normal work, complication rate and cost. Results: There were no statistical differences regarding patient characteristics between the two groups. Conversion to laparotomy was necessary in 5 patients (1.88%). Laparoscopic appendectomy was associated with a shorter hospital stay (1.5 d vs 2.5 d), lower incidence of wound infection (3.07% vs 8.29%,) &less analgesia requirement. The operative time was more (45.6 vs 24.5 min) and the cost of treatment was higher in the laparoscopic group. Conclusion: The laparoscopic technique is a safe and clinically beneficial operative procedure. It provides certain advantages over open appendectomy, ·including short hospital stay, decreased requirement .of postoperative analgesia, early food tolerance, and earlier return to normal activities, Where feasible, laparoscopy should be undertaken as the initial procedure of choice for most cases of appendicitis. Journal of Surgical Sciences (2013) Vol. 17 (1) : 7-13